2018
DOI: 10.1016/j.bja.2017.12.047
|View full text |Cite
|
Sign up to set email alerts
|

Carotid ultrasound measurements for assessing fluid responsiveness in spontaneously breathing patients: corrected flow time and respirophasic variation in blood flow peak velocity

Abstract: NCT 02843477.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
90
2
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 60 publications
(102 citation statements)
references
References 40 publications
2
90
2
3
Order By: Relevance
“…However, the gray‐zone analysis, with boundaries defined by the values associated with sensitivity of 90% and specificity of 90%, revealed that 50% of the patients were in the gray zone, limiting its usability in clinical practice. We found that the ðV peak was a poor predictor of hypotension, as it is affected by patients’ respiratory effort and patterns …”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…However, the gray‐zone analysis, with boundaries defined by the values associated with sensitivity of 90% and specificity of 90%, revealed that 50% of the patients were in the gray zone, limiting its usability in clinical practice. We found that the ðV peak was a poor predictor of hypotension, as it is affected by patients’ respiratory effort and patterns …”
Section: Discussionmentioning
confidence: 99%
“…Hossein-Nejad et al 25 reported that the carotid artery cFT decreased with hemodialysis in patients with chronic kidney disease, and the change in the cFT correlated with the ultrafiltrate removed. In a prospective observational study, Kim et al 12 reported that the cFT predicted fluid responsiveness with an AUROC of 0.84 in patients undergoing neurosurgery under general anesthesia. 12 However, the best cutoff value for predicting fluid responsiveness was 349.4 milliseconds in their study.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations